Intuitive remarks on diathesis (Atti del Sodalizio Glottologico Milanese, 2014)
Active, middle, and passive, as diatheses, are currently (and traditionally) defined in terms of the presumed semantic properties of their subjects. This paper spotlights limits and inadequacies of this viewpoint and claims the functional and syntactic nature of diathesis. KEYWORDS: syntax, diathesis, semantic properties, subject, grammatical functions